COVID-19 Salgını: Diyetisyenlerin Rolü ve Rehberler - Pekcan, Ayla Gülden (Türkiye Diyestisyenler Derneği, 2020)
Diyetisyenler klinik beslenme uzmanlarıdır ve sağlıklı, akut ve kronik hastalığı olan bireylerin, yaşlıların, farklı durumlarda risk altındaki toplum gruplarının beslenme gereksinimlerini desteklemek, beslenme durumlarını saptamak ve izlemek üzere özel eğitim almış tek meslek profesyonelidir. COVID-19 salgın sürecinde de diyetisyenlerin öncelikle bireylerin ve toplum gruplarının bağışıklık sisteminin güçlendirilmesi ve evde karantina sürecinde optimal beslenmenin desteklenmesi, hastanede yoğun bakım ünitelerinde hastaların beslenmesinin yönetiminde önemli rolü bulunmaktadır. Diyetisyenlerin COVID-19 salgını sürecinde beslenmenin yönetiminde kullanabileceği yayınlanmış rehberler bulunmaktadır.

Dietitians are the clinical nutrition experts and are the only professionals specifically trained to support the nutrition needsof healthy, acutely and chronically ill people with a wide range of conditions, to support and monitor the nutritional statusof populations at risk, including older adults. The core role that dietitians are playing during the COVID-19 pandemic, fromthe frontline in promoting optimal nutrition for supporting the immune system of the subjects and population groups andthe quarantine period at home, management of nutrition in intensive care unit patients. Published guidelines are availablefor the dietitians to be used during the COVID-19 pandemic.
COVID-19 Pandemic: Role of Dietitians and Guidelines
Keywords: Covid-19; diyetisyen; beslenme; rehberler